A sustainable system of systems approach: a new HFE paradigm. Issue 2 (1st February 2016) - Thatcher, Andrew; Yeow, Paul H.P.
Abstract : Sustainability issues such as natural resource depletion, pollution and poor working conditions have no geographical boundaries in our interconnected world. To address these issues requires a paradigm shift within human factors and ergonomics (HFE), to think beyond a bounded, linear model understanding towards a broader systems framework. For this reason, we introduce a sustainable system of systems model that integrates the current hierarchical conceptualisation of possible interventions (i.e. micro-, meso- and macro-ergonomics) with important concepts from the sustainability literature, including the triple bottom line approach and the notion of time frames. Two practical examples from the HFE literature are presented to illustrate the model. The implications of this paradigm shift for HFE researchers and practitioners are discussed and include the long-term sustainability of the HFE community and comprehensive solutions to problems that consider the emergent issues that arise from this interconnected world. Practitioner Summary: A sustainable world requires a broader systems thinking than that which currently exists in ergonomics. This study proposes a sustainable system of systems model that incorporates ideas from the ecological sciences, notably a nested hierarchy of systems and a hierarchical time dimension. The implications for sustainable design and the sustainability of the HFE community are considered.